Classification, biology and entomopathogenic fungi-based management and their mode of action against Drosophila species (Diptera: Drosophilidae): a review - Vivekanandhan, Perumal; Swathy, Kannan; Sarayut, Pittarate; Patcharin, Krutmuang (Frontiers in Microbiology, 2024)
This review provides a comprehensive analysis of the classification, biology, and management of Drosophila species (Diptera: Drosophilidae) with a focus on entomopathogenic fungi (EPF) as a biocontrol strategy. Drosophila species, particularly Drosophila suzukii, and Drosophila melanogaster have emerged as significant pests in various agricultural systems, causing extensive damage to fruit crops. Understanding their taxonomic classification and biological traits is crucial for developing effective management strategies. This review delves into the life cycle, behavior, and ecological interactions of Drosophila species, highlighting the challenges posed by their rapid reproduction and adaptability. The review further explores the potential of EPF as an eco-friendly alternative to chemical pesticides. The mode of action of EPF against Drosophila species is examined, including spore adhesion, germination, and penetration of the insect cuticle, leading to host death. Factors influencing the efficacy of EPF, such as environmental conditions, fungal virulence, and host specificity, are discussed in detail. By synthesizing current research, this review aims to provide valuable insights into the application of EPF and to identify future research directions for enhancing the effectiveness of EPF-based control measures against Drosophila species.